New South American species of Crossopalpus Bigot (Diptera: Hybotidae: Tachydromiinae), including biogeographical insights and a reinterpretation of female abdominal tergite 10 in Drapetidini - Freitas-Silva, Rafael A. P.; Ale-Rocha, Rosaly (Zootaxa, 2019)
Crossopalpus is a rather diverse genus of tachydromiine flies, but regionally the genus is nowhere very speciose. Knowledge on the South American Crossopalpus before this paper included two described species from Andean related habitats, with several biomes from the eastern part of the continent being completely unexplored. Herein, we describe four new species of Crossopalpus from eastern South America, namely: C. albivertex sp. nov., C. aliceae sp. nov., C. goliathus sp. nov., and C. xanthogaster sp. nov. New diagnoses and high quality photographs are made available for C. armipes (Bezzi, 1909) and C. pennescens (Melander, 1918), including some characters used for the first time to distinguish South American species. We provide a key for identification of the six South American species, discussion about the position of Crossopalpus in Drapetidini, and some biogeographical insights including preferred habitats and seasonality of the South American species. We discuss the apparent loss of tergite 10 in females of Drapetidini, introducing a reinterpretation where the sclerite may be present in some genera of the tribe, but fused to the cerci and/or sternite 10.